2020
DOI: 10.1002/path.5576
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in white matter disorders of the CNS: mechanisms and therapeutic opportunities

Abstract: Autophagy is a constitutive process that degrades, recycles and clears damaged proteins or organelles, yet, despite activation of this pathway, abnormal proteins accumulate in neurons in neurodegenerative diseases and in oligodendrocytes in white matter disorders. Here, we discuss the role of autophagy in white matter disorders, including neurotropic infections, inflammatory diseases such as multiple sclerosis, and in hereditary metabolic disorders and acquired toxic‐metabolic disorders. Once triggered due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 158 publications
0
6
0
Order By: Relevance
“…Depending on the environment, autophagy acts as a dual part in cancer [ 6 ], possibly reducing the viability of tumor cells or as a cytoprotective mechanism [ 7 ]. In some situations, autophagy can produce nutrients to provide energy for cells by constitutively eliminating defective proteins and organelles [ 8 ]. Conversely, autophagy can trigger cell death under certain conditions, such as over-regulation of autophagy or long-term exposure to autophagy [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the environment, autophagy acts as a dual part in cancer [ 6 ], possibly reducing the viability of tumor cells or as a cytoprotective mechanism [ 7 ]. In some situations, autophagy can produce nutrients to provide energy for cells by constitutively eliminating defective proteins and organelles [ 8 ]. Conversely, autophagy can trigger cell death under certain conditions, such as over-regulation of autophagy or long-term exposure to autophagy [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In some situations, autophagy can produce nutrients to provide energy for cells by constitutively eliminating defective proteins and organelles [ 8 ]. Conversely, autophagy can trigger cell death under certain conditions, such as over-regulation of autophagy or long-term exposure to autophagy [ 8 ]. Autophagy has played an important intermediary role in terms of resistance to radiation, chemotherapy, and targeted agents [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several pieces of evidence indicated that disturbed autophagy plays a pivotal role in the pathogenesis of white matter disorders and therapeutics targeting autophagy may be a promising strategy [ 33 ]. Our previous studies have demonstrated the fundamental aspect of GLD in that both impaired autophagy and dysfunction of UPS lead to the broad deposition of p62- and ubiquitin-aggregates resulting in the death of oligodendrocytes in the central nervous system [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microglia/macrophages show the highest phagocytic activity, but also astrocytes contribute to myelin clearance [38]. The internalization and turnover of myelin lipids and proteins in these cells, which involve autophagic processes [39][40][41][42], then contributes to the resolution of neuroinflammation [43,44]. As myelin debris and a proinflammatory environment strongly inhibit oligodendroglial differentiation [45], the lysosomal degradation of myelin lipids and proteins in phagocytes is a prerequisite for repair of demyelinated lesions.…”
Section: Cholesterol Metabolism During Demyelination and Remyelinationmentioning
confidence: 99%